Programa educativo aprender con proyectos para mejorar el pensamiento crítico en estudiantes del primer nivel de la carrera de ciencias sociales de la Facultad de Educación UNAP Iquitos 2021 - Avidón Lachuma, Margarita (2024)
Using a quasi-experimental design, the authors of the thesis Educational Research Program, to Strengthen Research Skills in Students of the Fourth Level of the Specialty in Philosophy and Psychology of the UNAP, Iquitos 2019, Evaluative Research compared the results of a group of 30 fourth-year students who participated in the Program with the results of another group of 30 students who did not. Based on the findings from the analysis and comparison, it was determined that students in the fourth year of the Faculty of Education Sciences and Humanities benefited from the Investigative educational program by developing their investigative skills. ONE P. 2021. A substantial improvement from pre- to postest scores (15 and 14) is indicative of the success of the educational intervention. Students in their fourth year of psychology and philosophy at the Faculty of Education Sciences and Humanities showed a statistically significant improvement in their investigative skills between their pre- and post-test scores (15,14).